Dialog antar Iman dan Kerja Sama Demi Harmoni Bumi - Media Zainul Bahri (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2011)
This paper will explain the importance of pluralism, or at least to appreciate inclusivism as understanding and practice of interfaith relations in the global era. Today, to be exclusive or to isolate ourselves in religious views is no longer relevant. Adopting pluralism or inclusivism as religious understanding can be a good theological capital for the enforcing inter-faith dialogues and cooperation, ethical and humanitarian cooperation.Keywords: Exclusive, inclusive, pluralistDOI: 10.15408/ref.v13i1.993